It's the Easter Beagle, Charlie Brown [videorecording (DVD)] - Guaraldi, Vince (Distributed by Warner Home Video, 2008)
Charlie, Sally, Lucy and the rest of the gang are getting ready for Easter, but Linus insists no preparation is necessary. The Easter Beagle will take care of everything!